Peran Mahasiswa Magang dalam Mendukung Pelayanan Publik di Kelurahan Tarok Dipo - Oktavia Batrila (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the role of student interns in supporting public services in Tarok Dipo Village. In Tarok Dipo Village itself, there is still a shortage of workers to serve the community, resulting in less than optimal services. The presence of student interns is expected to be a form of real contribution from higher education in improving the quality of governance at the local level. This study uses a qualitative descriptive method with data collection techniques through observation, library literature and documentation. The results show that student interns play a role in helping smooth administration, providing innovation in data management, and improving the quality of public services through mentoring and counseling. In addition, the presence of student interns can also encourage village officials to be more adaptive in utilizing technology. Thus, student interns have a significant contribution in strengthening public services in the village.